ANALISIS “SENSE OF COMMUNITY” MAHASISWA PROGRAM STUDI BIMBINGAN KONSELINGDI PTKIN BERDASARKAN STATUS INSTITUSI DAN SEKOLAH ASAL - Amirah Diniaty (Fakultas Tarbiyah dan Keguruan UIN Imam Bonjol Padang, 2015)
Sense of community (SOC) on student self Prodi BK in Perguruan Tinggi Keagamaan Islam Negeri (PTKIN) will lead to a sense of empathy, mutual aid between the academic community in order to achieve success together in learning and career as a counselor later,.This study is a comparative study using factor analysis with Kruskal Willis. The study population was student of Counseling 4th semester of the academic year 2014/2015 in PTKIN different status is IAIN Imam Bonjol Padang, State Islamic University Syarif Kasim Sultan Riau and IAIN Jamil Jambek Bukittinggi. These samples included 136 people. Data were collected by questionnaire and processed using SPSS. The results showed differences in student scores SOC Prodi BK based on the status of their home institutions and schools are boarding schools, high schools, and vocational MAN.